Prognostic Value of Interval Between the Initiation of Neoadjuvant Treatment to Surgery for Patients With Locally Advanced Rectal Cancer Following Neoadjuvant Chemotherapy, Radiotherapy and Definitive Surgery - Wan, Xiang-Bo; Zhang, Qun; Chen, Mo; Liu, Yanping; Zheng, Jian; Lan, Ping; He, Fang (Frontiers in Oncology, 2020)
Background: The addition of intensive preoperative chemotherapy and using of a longer waiting period between neoadjuvant radiotherapy and total mesorectal excision (TME) surgery lengthen the time interval from the initiation of neoadjuvant treatment to definitive surgery in patients with locally advanced rectal cancer (LARC). Here, we evaluated the prognostic value of different time intervals between the initiation of neoadjuvant treatment to TME surgery for LARC. Methods: A total of 2,267 patients with LARC, who received neoadjuvant radiochemotherapy and TME surgery, between January 2010 through December 2018 were recruited. The entire cohort was divided into 4 subgroups based on total-time-to surgery, defined as the time interval between initiation of neoadjuvant treatment and TME surgery (TTS): <13 weeks (TTS-1), 13 to <15 weeks (TTS-2), 15 to <17 weeks (TTS-3), ≥17 weeks (TTS-4). Overall survival (OS), disease-free survival (DFS), distant metastasis-free survival (DMFS), and local recurrence-free survival (LRFS) rates in different TTS subgroup patients were compared, and hazard ratios (HR) for different demographic and clinicopathological variables, including TTS, were calculated to determine their prognostic significance. Results: The median follow-up time was 42.0 (range, 5–162) months. The 3-year OS, DFS, DMFS, and LRFS rates were 87.0, 79.4, 80.9, and 93.8%, respectively. The varied OS, DFS, and DFMS rates were detected among these different TTS subgroups (P = 0.010, P < 0.001, and P < 0.001, respectively). Particularly, the lower survival outcome was mainly observed at patients in the shortest TTS group (TTS-1). Cox regression analysis confirmed that the only significant positive independent prognostic factor for 3-year DFS was a longer TTS (TTS 2–4 vs. TTS-1; HR 0.884, 95% CI 0.778–0.921, P < 0.001), while the significant negative independent prognosticfactors were moderate to poor tumor differentiation (vs. well-differentiated; HR 1.191, 95% CI 1.004–1.414, P = 0.045) and clinical N1-2 stage (vs. N0 stage; HR 1.190, 95% CI 1.052–1.347, P = 0.006). Conclusion: For patients with LARC, an interval between the initiation of neoadjuvant treatment and TME surgery of longer than 13 weeks is associated with favorable disease-free survival.